Mesoscopic anatomy and histotopography of the left atrial appendage walls in human fetal heart - A. A. Gaponov; I. D. Ufimtseva; E. G. Dmitrieva; D. K. Kuznetsov; V. I. Pryakhina; A. A. Iakimov (Сибирский научный медицинский журнал, 2024)
Normal anatomy of the left atrial appendage (LAA) of human fetus is of a great importance for fetal cardiac surgery and heart bioprinting. Aim of the study was to clarify the mesoscopic anatomy and histotopography of different parts of the LAA walls in normal human fetuses of 16–22 gestation weeks. Material and methods. We prepared serial histotopograms of the left atrial appendages from 10 normal human fetal hearts stained by Masson trichrome, orcein and fast green. We studied slides by means Olympus CX microscope, TOUPCAM U31S digital camera, and ADF-Image program for measuring. Using a Carl Zeiss EVO LS 10 scanning electron microscope at a magnification of 15–5000 times, three samples were examined using the freeze-chip method. Results. Having measured the outer walls of the LAA intertrabecular spaces, we found that at the level of the middle third of the left atrium, their thickness is minimal in the posterior wall (80 [61–97] μm) (median [lower quartile; upper quartile]), thickness in the anterior wall is 142.9 ± 33.2 μm (mean ± standard deviation) (101 [79–192] μm). At the level of the coronary sulcus, the same parameters were 143.7 ± 23.6 µm (147.5 [90–180] µm) and 137.4 ± 33.9 µm (101 [68–195] µm), respectively. Downward, LAA posterior wall increased about 1.8 in thickness, whereas the thickness of the anterior wall was the same. The endocardium showed the same thickness in all locations. Microanatomically, the LAA myocardium never discovered to build from distinct layers but “anatomical syncytium” or seldom bundles. Collagen and elastic layers were common for endocardium, rare for epicardium. Endocardial elastic fibers interweaved in the underlying collagen so the distinct boundary lacks there. Conclusions. Mesoscopic and microanatomical features of LAA walls in human fetus consist of variable thickness at different levels, unlayered but “syncytial” myocardium, muscleless areas, elastic and collagen layers of the endocardium.